Function of vasohibin-2 and the mechanism of alternative splicing in triple-negative breast cancer - WANG Wei; WANG Hongli; ALIBIYATI·i Ain; YILIYAER· Rousu; NUER AYI; YANG Liang (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Objective·To explore the role of vasohibin-2 (VASH2) in the regulation of proliferation and metastasis of triple-negative breast cancer (TNBC) cells, and explore the mechanism of VASH2 in the occurrence and development of TNBC through regulation of gene expression and alternative splicing.Methods·TCGA-GTEx was used to analyze the expression of VASH2 in TNBC. VASH2 methylation levels in TNBC were also analyzed. VASH2 was overexpressed in the MDA-MB-231 human TNBC cell line and transcriptome sequencing was performed. Differentially expressed genes and alternatively spliced genes regulated by VASH2 were analyzed to explore the mechanism of action of VASH2 in TNBC.Results·VASH2 was significantly overexpressed in TNBC compared to the normal tissues. Hypomethylation of the VASH2 gene was implicated in the upregulation of VASH2 expression in TNBC. Overexpression of VASH2 caused significant differential expression of 81 genes, of which 23 genes were up-regulated and 58 genes were down-regulated. Genes with significantly altered alternative splicing levels due to VASH2 overexpressed were enriched in cell cycle and p53 signaling pathways.Conclusion·VASH2 regulates the alternative splicing of TNBC oncogenes and promotes TNBC occurrence and development.